2015
DOI: 10.1371/journal.pone.0119102
|View full text |Cite
|
Sign up to set email alerts
|

Significant In Vivo Anti-Inflammatory Activity of Pytren4Q-Mn a Superoxide Dismutase 2 (SOD2) Mimetic Scorpiand-Like Mn (II) Complex

Abstract: BackgroundThe clinical use of purified SOD enzymes has strong limitations due to their large molecular size, high production cost and immunogenicity. These limitations could be compensated by using instead synthetic SOD mimetic compounds of low molecular weight.Background/MethodologyWe have recently reported that two SOD mimetic compounds, the MnII complexes of the polyamines Pytren2Q and Pytren4Q, displayed high antioxidant activity in bacteria and yeast. Since frequently molecules with antioxidant properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Moreover, it has been recognized that MAPKs play a pivotal role in the pathogenesis of many inflammatory disorders [ 27 ]. A study demonstrated that manganese (II) complex diminishes the gene expression and protein secretion of cytokines induced by LPS in THP-1 macrophages, probably due in part to the inactivation of the MAPK signaling pathway [ 28 ]. Recent in vitro studies in RAW 264.7 cells have shown that p38 MAPK is involved in NF-κB activation [ 29 ], and our data also proved this hypothesis in that the p38 inhibitor, SB203508, inhibited p65.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been recognized that MAPKs play a pivotal role in the pathogenesis of many inflammatory disorders [ 27 ]. A study demonstrated that manganese (II) complex diminishes the gene expression and protein secretion of cytokines induced by LPS in THP-1 macrophages, probably due in part to the inactivation of the MAPK signaling pathway [ 28 ]. Recent in vitro studies in RAW 264.7 cells have shown that p38 MAPK is involved in NF-κB activation [ 29 ], and our data also proved this hypothesis in that the p38 inhibitor, SB203508, inhibited p65.…”
Section: Discussionmentioning
confidence: 99%
“…The SGBS cell line, provided by Dr. Wabitsch (University of Ulm, Germany) and Lisa-2 cells, provided by Dr. Möller (University of Ulm, Germany), were used as cellular models of human subcutaneous and visceral pre-adipocytes, respectively, and were induced to differentiate as described [17] . THP-1 cells (a human monocytic cell line; ATCC, Rockville, MD) were induced to differentiate to macrophages with PMA as previously described [18] . The human myogenic cell line LHCN-M2 was used as a cellular model of human myoblasts.…”
Section: Methodsmentioning
confidence: 99%
“…Scorpiand type aza-macrocyclic ligands, that is aza-macrocyclic ligands with coordinating tails [1], and their metal complexes have attracted considerable interest thanks to the numerous uses they have been tested for, including but not limited to various biomedical applications [2,3] (MRI contrast agents [4,5], radioisotopes complexation and radiolabelling [6][7][8][9], radiotherapy [10][11][12][13][14], chelation therapy [15][16][17], antiproliferative treatments [18][19][20][21], enzyme mimicking [22][23][24][25][26][27][28][29]), catalysis [30][31][32][33][34][35][36] and chemosensing [37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%